EXPLORING TEACHERS’ EXPERIENCE IN UTILIZING SLIDES PRESENTATION TOOLS TO ENHANCE ENGLISH TEACHING - Prasojo, Anggit; Afrianto Daud; Masyhur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study explored English teachers’ experiences in utilizing slide presentation tools to enhance English teaching at SMAN 8 Pekanbaru. Specifically, it examined how slides were employed to organize lessons, support comprehension, manage classroom activities, and motivate students. A qualitative case study was conducted with five purposively selected teachers, and data from semi-structured interviews were analyzed thematically to ensure depth and credibility. The findings highlight three interrelated dimensions: instructional, technological, and creative-motivational experiences. Instructionally, slides enabled teachers to align content with learning objectives, maintain lesson flow, and optimize classroom management. Technologically, teachers demonstrated strong familiarity with tools such as PowerPoint and Canva, showing confidence and adaptability when facing challenges such as technical disruptions. Creatively, the integration of visuals, animations, and multimedia features enhanced learner engagement while requiring careful balance between aesthetics and clarity. These insights suggest that slide tools function not merely as visual support but as integral pedagogical instruments that shape instructional delivery, foster comprehension, and sustain engagement. The study contributes to English education by underscoring the importance of digital competence and instructional innovation, offering implications for professional development programs in English Teaching contexts.